ANALISIS PROFITABILITAS TANAMAN KARET (Hevea brasiliensis L) PADA PT. PERKEBUNAN NUSANTARA IX (PERSERO) KEBUN BALONG/BEJI/KALITELO KABUPATEN JEPARA - Munafidza Munafidza; Suprapti Supardi; Eka Dewi Nurjayanti (MEDIAGRO, 2015)
PT. Perkebunan Nusantara IX (Persero) Balong/Beji/Kalitelo Plantation is located in Keling and Kembang District Jepara Regency and Dukuhseti District Pati Regency. Balong/Beji/Kalitelo Plantation cultivate rubber, cocoa and coconut plant. Plantation, in the operations, especially rubber plants, face the fluctuations of selling price, the amount of production and production costs. The fluctuations of these variables will affect the level of profitability that would be achieved by the company. This research aims to determine the profitability of rubber cultivation and sensitivity when there are fluctuations of price, the amount of production and production costs. This research used descriptive method, with the technique implementation using the case method. The research location were selected by purposive method that is PT. Perkebunan Nusantara IX (Persero) Balong/Beji/Kalitelo Plantation Jepara Regency. Data analysis method used the profitability analysis (NPV, Gross B/C and Profitability Ratio) and sensitivity analysis. The data that used in this research are the production data, production costs and selling prices at 2009-2013. The results showed that the cultivation of rubber in the PT. Perkebunan Nusantara IX (Persero) Balong/Beji/Kalitelo Plantation Jepara Regency is advantageous to be carried because the NPV values is 313,785,213,295.00; Gross B/C values is 2.41; and PR values is 11.15. Company will still obtain earnings eventhough there are the fluctuation of variable amount production until 15%, selling price until 30% and production costs until 25%. Besides, the fluctuation of variables simultaneously, that are selling price until 30% and production costs until 25%; the selling price until 30% and the amount production until 15%; amount production until 15% and production costs until 25%, showed that the company still obtain earning. Based on the research results, there are two suggestions for this company; first, replace less productive plants with new plants;  and the second, maximizing high-grade product quality.   Keywords: Profitability, PTPN, rubber plant.